The outcome of reoperative pulmonary endarterectomy surgery. (23rd January 2018) - Ali, Jason M; Dunning, John; Ng, Choo; Tsui, Steven; Cannon, John E; Sheares, Karen K; Taboada, Dolores; Toshner, Mark; Screaton, Nick; Pepke-Zaba, Joanna; Jenkins, David P
Abstract: OBJECTIVES: Pulmonary endarterectomy (PEA) is the treatment of choice for patients with chronic thromboembolic pulmonary hypertension (PH). Despite excellent outcomes following PEA, a small proportion of patients have residual proximal disease or present with recurrent chronic thromboembolic PH and may benefit from further surgery. The aim of this study was to analyse outcomes following reoperative PEA at a high-volume national tertiary referral centre for the management of chronic thromboembolic PH. METHODS: This retrospective analysis was performed using our prospectively maintained PH database to identify all patients who underwent reoperative PEA surgery between the commencement of the programme in 1997 and January 2017, and the patients' data were collected for analysis. RESULTS: Twelve patients underwent reoperative PEA during the period of study. The mean interval between primary procedure and reoperative procedure was 6.3 years. Significant improvements were observed in pulmonary haemodynamics following reoperative PEA. Mean pulmonary arterial pressure decreased from 46.8 to 29.8 mmHg ( P  < 0.0001) and pulmonary vascular resistance decreased from 662 to 362 dyne·s·cm −5 ( P  = 0.0007). A significant functional improvement in the 6-min walking test distance was also observed, increasing from 327 to 460 m at 6 months postoperatively ( P  = 0.0018). Median length of hospital stay was 12 days. In-hospital mortality was 8.3% with 1-year survival of 83.3%. CONCLUSIONS: Reoperative PEA is technically possible and relatively safe, achieving good functional and physiological outcomes. Patients must be carefully selected by a multidisciplinary team, and surgery should be performed in experienced centres.